Do Subjective Memory Complaints Herald the Onset of Mild Cognitive Impairment in Parkinson Disease?. (December 2014) - Erro, Roberto; Santangelo, Gabriella; Barone, Paolo; Picillo, Marina; Amboni, Marianna; Longo, Katia; Giordano, Flavio; Moccia, Marcello; Allocca, Roberto; Pellecchia, Maria Teresa; Vitale, Carmine
Background: Longitudinal studies on healthy participants have shown that subjective memory impairment (defined as subjective cognitive complaints with normal cognitive objective performance) might be a strong predictor of mild cognitive impairment (MCI). Parkinson disease (PD) also manifests cognitive disturbances, but whether subjective memory complaints may predict the development of MCI in PD has not yet been explored. Methods: We prospectively screened newly diagnosed, untreated patients with PD in order to evaluate whether subjective memory complaints may predict development of MCI over a 2-year follow-up evaluation. Results: We enrolled 76 de novo untreated patients with PD. Of the 76 patients, 23 (30.3%) complained memory issues. Among the patients cognitively unimpaired at baseline, those with subjective complaints were more likely to develop MCI at follow-up. The regression model confirmed that presence of subjective memory complaints at baseline was an independent predictor of development of MCI at follow-up. Discussion: This is the first prospective study to explore the relationship between subjective and objective cognitive deficits in newly diagnosed, untreated patients. Our results provide preliminary evidence that subjective memory complaints might predict future development of MCI.